2017
DOI: 10.1186/s12903-017-0431-0
|View full text |Cite
|
Sign up to set email alerts
|

Five years’ follow-up of dental fear and anxiety, experience of dental care and oral health behaviour in Swedish preterm and full-term adolescents

Abstract: BackgroundThere is rising concern about how preterm birth affects long-term health later in life. The various effects that preterm birth have on developmental outcomes, cognitive profiles and medical health may also affect levels of cooperation in the dental care situation in addition to general oral health and other oral health-related habits. Oral health is an integral part of one’s general health and well-being; however, less is known about how prematurity affects oral health and other related areas such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 32 publications
2
22
0
2
Order By: Relevance
“…A list of other questions used in this study can be found in Table . However, the questionnaire also contained other items with focus on dental fear, experience of dental care and oral health behaviour …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A list of other questions used in this study can be found in Table . However, the questionnaire also contained other items with focus on dental fear, experience of dental care and oral health behaviour …”
Section: Methodsmentioning
confidence: 99%
“…21 However, the questionnaire also contained other items with focus on dental fear, experience of dental care and oral health behaviour. 22 The questionnaire included also the Swedish version of Beck Youth Inventories (BYI) 23 includes five self-report inventories for individuals between 7 and 18 years. In a study from 2009, the BYI showed good internal consistency and test-retest stability.…”
Section: Questionnairementioning
confidence: 99%
“…Psychology Mejare, 2007;Vingilis, Wade, & Seeley, 2007). The connection between general health, disabilities, and oral health is well-known (Blomqvist, Holmberg, Fernell, Ek, & Dahllof, 2006;Brogardh-Roth et al, 2017;Carlsson, Hakeberg, Blomkvist, & Wide Boman, 2013). Oral health problems, such as poor oral hygiene, and gingival health has been noted in adolescents with poor general health and/or disabilities.…”
Section: Self-rated Healthmentioning
confidence: 99%
“…Entre as características psicológicas dos adolescentes estão a busca de identidade, os desequilíbrios e instabilidades extremas, a alternância de períodos de altivez, introversão, audácia, timidez, falta de coordenação, sentimento de urgência, desinteresse e apatia, conflitos afetivos e crises religiosas (ABERASTURY e KNOBEL, 2008). Assim, o impacto das doenças bucais pode ser percebido de forma mais ampla, como um obstáculo para o desenvolvimento social dos indivíduos.Esses jovens, em transição para a vida adulta, passam a ter mais responsabilidade sobre diferentes aspectos das suas vidas, inclusive sobre sua saúde geral e bucal, de forma a evoluírem de recebedores de cuidados para potenciais cuidadores(BROGARDH-ROTH et al, 2017) MEULENERS et al (2003),. ao estudarem os fatores associados à percepção da qualidade de vida em adolescentes, destacaram a importância dos fatores psicológicos e sociais para o bem-estar deste grupo, além de fatores como saúde, ambiente (segurança, local de moradia, local de estudo e vizinhança) e oportunidades de crescimento.Dados relativos à adaptação desses adolescentes às mudanças e fatores que influenciam o sucesso da transição ou dificuldades encontradas devem incluir indicadores subjetivos de saúde, como a felicidade.…”
unclassified
“…A felicidade pode funcionar como uma espécie de "amortecedor" para o stress associado ao período(MAHON e YARCHESKI, 2002). Como aproximadamente metade das desordens mentais têm suas primeiras manifestações antes dos 14 anos(KESSLER et al, 2005;BOLTON et al, 2016), é importante que se façam estudos nessa faixa etária a fim de promover sua saúde mental.1.9 ADOLESCÊNCIA E SAÚDE BUCAL O estudos sobre as percepções dos jovens sobre sua saúde bucal durante a transição para a vida adulta são limitados(JOHANSSON e OSTBERG, 2015;BROGARDH-ROTH et al, 2017). Os adolescentes são considerados pela OMS como um grupo chave para estudos epidemiológicos de saúde bucal(WHO, 1986).…”
unclassified